Pola Relasi Kuasa Negara dan Kelompok Tambang Minyak Ilegal (Studi Kasus Tambang Minyak Kecamatan Keluang Kabupaten Musi Banyuasin Sumatera Selatan) - Wahyudi, Choirul (Ampera: A Research Journal on Politics and Islamic Civilization, 2020)
This study will describe how the pattern of relations in the management of illegal oil mines in Keluang District with two problem formulations, first what are the factors that shape the power relations between the State and the illegal oil mining group in Keluang District. The second is how the role of each actor and its influence in the case of illegal oil mining in Keluang District? To answer the two problem formulations above, researchers use the theory of rent seeking from Gordon Tullock. The method used in this research is qualitative method. The approach that will be used to support this research is to use a case study approach. In this study, the data will be divided into two types, namely primary and secondary data. Primary data is data obtained in the field through interviews and direct observation at the research site. Secondary data is data obtained from books, papers and documents related to this research. Data analysis used in this study is Analysis Interactive Model from Miles and Huberman which divides the steps in data analysis activities with several parts, namely data collection, data reduction, data presentation, and drawing conclusions or verification. The presence of illegal oil mines in Keluang District raises a sign where the presence and how the role of the State especially the government involved in the management of natural resources in the case of illegal oil mining in Keluang District.